L’impérialisme humanitaire de Michael Ignatieff : le cas d’un « liberal hawk » - Pierre Guerlain (Revue LISA)
Michael Ignatieff, a former Harvard professor who is now active in Canadian politics, represents a school of thought which may be called humanitarian imperialism or liberal imperialism whose most famous representative in Europe is Bernard Kouchner. He argues for US interventions in the world (Kosovo, Afghanistan, Iraq) on account of UN weakness and unwillingness to stop massacres or genocides. In his calls for the US to assume this new burden, Ignatieff mentions all the arguments usually invoked against empires and imperialism only to reject them in a rhetorical twist. He is one of the most articulate advocates of military intervention with a clear conscience. Though he often ends up in agreement with neoconservative or neoliberal imperialists his justifications are more intellectual and convoluted and therefore address a different audience.